Vercelli Homily XXI, Smaragdus of Saint- Mihiel’s Commentary on the Rule of Benedict, and the Laudes Regiae - Wright, Charles Darwin (Revue bénédictine, 2024)
A litany of divine epithets in the Old English Vercelli Homily XXI has a previously unrecognized source in Smaragdus of Saint-Mihiel’s Expositio in Regulam S. Benedicti. Smaragdus’s litany in turn has a previously unrecognized partial source in the Carolingian Laudes regiae, from which Smaragdus drew multiple epithets. The form of the litanies in all three texts (representative clauses are ‘he is ure strengð’ / ‘Christus fortitudo nostra’ / ‘Fortitudo nostra. Christus uincit’) echoes what has been called the ‘litany of possessives’ common in devotional treatises and private prayers. The use in Vercelli XXI of Smaragdus’s commentary on the Rule of Benedict suggests that the common author of Vercelli Homilies XIX-XXI was a Benedictine monk active during the early years of the Benedictine Reform movement in England (beginning in the 960s), not long before the Vercelli Book itself was compiled (probably before 975). This conclusion is not incompatible with previous arguments that certain other homilies in the Vercelli Book may have been composed by or for secular clergy, since the homilies derive from multiple exemplars of varying dates, some of which undoubtedly pre-dated the Benedictine Reform.